1999
DOI: 10.1006/viro.1999.9695
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, Genetic Stability, and Protective Efficacy of a Recombinant, Chimeric Yellow Fever-Japanese Encephalitis Virus (ChimeriVax-JE) as a Live, Attenuated Vaccine Candidate against Japanese Encephalitis

Abstract: Yellow fever (YF) 17D vaccine virus, having a 60-year history of safe and effective use, is an ideal vector to deliver heterologous genes from other medically important flaviviruses. A chimeric YF/Japanese encephalitis (JE) virus (ChimeriVax-JE virus) was constructed by insertion of the premembrane and envelope (prME) genes of an attenuated human vaccine strain (SA14-14-2) of Japanese encephalitis (JE) virus between core and nonstructural (NS) genes of a YF 17D infectious clone. The virus grew to high titers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 29 publications
12
131
0
Order By: Relevance
“…The PUO-218 virus differs from NGC virus in two amino acids in prM (residues 55 and 125, respectively L and I in PUO-218 instead of F and T in NGC) and six amino acids in the E protein (amino acid 71 is E in PUO-218 and D in NGC [71 E3D], 126 E3K, 141 V3I, 164 V3I, 402 F3I and 484 I3V) ( Table 2). In Table 3 nucleotide and amino acid differences within the nonstructural (NS) genes of ChimeriVax-D2, ChimeriVax-JE (9), and the parent YF 17D virus (22) are shown. There were six nucleotide differences between ChimeriVax-D2 and YF 17D.…”
Section: Resultsmentioning
confidence: 99%
“…The PUO-218 virus differs from NGC virus in two amino acids in prM (residues 55 and 125, respectively L and I in PUO-218 instead of F and T in NGC) and six amino acids in the E protein (amino acid 71 is E in PUO-218 and D in NGC [71 E3D], 126 E3K, 141 V3I, 164 V3I, 402 F3I and 484 I3V) ( Table 2). In Table 3 nucleotide and amino acid differences within the nonstructural (NS) genes of ChimeriVax-D2, ChimeriVax-JE (9), and the parent YF 17D virus (22) are shown. There were six nucleotide differences between ChimeriVax-D2 and YF 17D.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mice and monkey models have shown that this chimeric vaccine was highly immunogenic and protects the animals against lethal JEV i.c. challenge (Monath et al, 2000;Guirakhoo et al, 1999;Monath et al, 1999). Phase I and II clinical trials of the vaccine have been carried out and it was found to be well tolerated and induced neutralizing antibodies in 100% of naïve and yellow fever virus immune participants.…”
Section: H2-t23mentioning
confidence: 99%
“…Currently, three JEV vaccines are in use (Guirakhoo et al, 1999 ;Chang et al, 2000): (i) a formalin-inactivated, mouse brain-derived vaccine, based on the wild-type Nakayama or Beijing-1 strains, has been used internationally since the 1960s; (ii) a cell culture-derived inactivated vaccine; (iii) a cell culture-derived live attenuated vaccine, in China only. All vaccine types were developed from GIII JEV strains.…”
Section: Japanese Encephalitis Vaccinementioning
confidence: 99%